PENGARUH KAMPANYE #DIET KANTONG PLASTIK TERHADAP SIKAP KHALAYAK MENGURANGI KETERGANTUNGAN TERHADAP KANTONG PLASTIK - ARIEF KHALIFATUR ROHMAN; SRI EKOWATI P (Program studi Ilmu Komunikasi Fakultas Ilmu Komunikasi Universitas Persada Indonesia YAI, 2021)
This study discusses the effect of the #diet plastic bag campaign on public attitudes to reduce dependence on plastic bags. The purpose of this study is to determine how much influence the # diet plastic bag campaign has on public attitudes to reduce dependence on plastic bags. The theory used in this research is the theory of social integration. The concepts used are communication, social campaigns, attitudes and plastic waste. The research method used is a survey method to find out how much influence it has. The technique of collecting data through a questionnaire with 100 respondents, namely Followers Instagram @IDDKP.The results of this study indicate a correlation of 71.9% and the conclusion of this study is the effect of the plastic bag # diet campaign on public attitudes to reduce dependence on plastic bags. the meaning. The #diet plastic bag campaign has a major effect on the attitudes of the public to reduce dependence on plastic bags.